A169: Cumulative Long‐Term Safety, Efficacy and Patient‐Reported Outcomes in Children With Juvenile Idiopathic Arthritis Treated With Intravenous Abatacept: Up to 7 Years of Treatment. Issue 11 (March 2014) - Lovell, Daniel J.; Ruperto, Nicolino; Mouy, Richard; Paz, Eliana; Rubio‐Perez, Nadina; Silva, Clovis A.; Abud‐Mendoza, Carlos; Burgos‐Vargas, Ruben; Gerloni, Valeria; Melo‐Gomes, Jose A.; Magalhaes, Claudia Saad; Chavez‐Corrales, Jose; et al.
Abstract : Background/Purpose: The long‐term efficacy and safety of intravenous abatacept in patients (pts) with juvenile idiopathic arthritis (JIA) have been reported previously from the Phase III AWAKEN trial (1 2 ). Here, we report efficacy, safety and pt‐reported outcomes from the open‐label, long‐term extension (LTE) of AWAKEN, with up to 7 years of follow‐up. Methods: Pts entered the LTE if they were JIA ACR 30 non‐responders (NR) at the end of the 4‐month lead‐in period (abatacept only), or if they received abatacept or placebo (pbo) in the 6‐month double‐blind (DB) period. The Child Health Questionnaire was used to evaluate health‐related quality of life (HRQoL); physical (PhS) and psychosocial (PsS) summary and pain scores were analyzed. Pain was assessed by parent global assessment using a 100 mm visual analog scale. Efficacy and HRQoL evaluations are reported up to Day 1765 ( Year 5.5). Safety is presented for the cumulative period (lead‐in, DB and LTE), for all pts who received abatacept during the LTE. Results: Of the 153 pts entering the LTE (58 from DB abatacept group, 59 from DB pbo group, 36 NR), 69 completed the trial (29 abatacept, 27 pbo, 13 NR). For pts treated in the LTE, mean (range) exposure to abatacept was 53.6 (5.6–85.6) months. During the LTE, incidence rates of AEs and serious AEs per 100 pt‐years were 209.1 and 5.6. Thirty pts (19.6%) had serious AEs; most were unrelated and were musculoskeletal (8.5%) or infectious events (6.5%). No malignancy was reported. There was one death (accidental; unrelated). At Day 169, JIA ACR 50 and 70 response rates were 79.3% and 55.2% in the abatacept group, and 52.5% and 30.5% in the pbo group; 31.0% and 10.2% of pts in the abatacept and pbo groups, respectively, had inactive disease. By Day 1765, JIA ACR 50 and 70 response rates were 93.9% and 78.8% in the abatacept group, and 80.0% and 63.3% in the pbo group; 51.5% and 33.3% had inactive disease. In the NR group, 69.2% and 53.8% of pts achieved JIA ACR 50 and 70 responses at Day 1765, and 30.8% had inactive disease. In pts who entered the LTE, mean baseline PhS scores were below the range for healthy children (abatacept 30.2, pbo 31.0, NR 29.5). At Day 169, 38.3% of pts had reached a PhS score >50 ((1 ). By the end of the LTE, 43.5% of pts had reached a PhS score >50. At baseline, mean PsS scores for those who entered the LTE were slightly lower than the mean for healthy children (abatacept 43.5, pbo 44.2, NR 47.0). At Day 169, 54.9% of pts had a PsS score >50 (1 ). By Day 1765, 58.1% of pts had reached a PsS score >50. At baseline, the mean pain score was 42.9. By Day 169, 13.9% of pts were considered pain free (pain score = 0); this was maintained over the LTE (1 ). Conclusion: Long‐term treatment with abatacept for up to 7 years was associated with consistent safety, and sustained clinical efficacy and quality‐of‐life benefits in patients with JIA who remained on therapy.